Rhizosphere microbial functional traits associated with basal stem rot suppression in oil palm (Elaeis guineensis) - EVAN PURNAMA RAMDAN; GIYANTO GIYANTO; ARIEF HARTONO; SRI HENDRASTUTI HIDAYAT; WIDODO WIDODO (Asian Journal of Agriculture, 2026)
Abstract. Ramdan EP, Giyanto, Hartono A, Hidayat SH, Widodo. 2026. Rhizosphere microbial functional traits associated with basal stem rot suppression in oil palm (Elaeis guineensis). Asian J Agric 10 (1): g100105. https://doi.org/10.13057/asianjagric/g100105. This study aimed to investigate the abundance, diversity, and functional characteristics of rhizospheric microbial communities associated with different levels of Basal Stem Rot (BSR) disease incidence in oil palm plantations, with the understanding that the observed relationships represent associations rather than causal effects. Rhizospheric microbial communities play an essential role in soil health and disease suppression in oil palm plantations. Fifteen composite soil samples were collected from three field blocks with low, moderate, and high BSR incidence in the Rejosari Unit, PT Perkebunan Nusantara VII, Lampung, Indonesia. Microbial populations were quantified using standard plate counts, while diversity indices were assessed using the Shannon-Wiener, evenness, and dominance indices based on morphospecies counts. The results showed that total microbial, bacterial, and fungal populations were significantly higher in soils with low disease incidence (4.99×10⁷, 4.94×10⁷, and 5.18×10⁵ CFU g-¹, respectively) compared to moderate and high categories. Soils with low BSR incidence also exhibited greater microbial and bacterial diversity (H′=1.07 and 0.74) and lower dominance, indicating a more balanced community structure. Non-pathogenic, antagonistic, and Volatile Organic Compound (VOC)-producing microbes predominated in low-incidence soils, contributing to natural disease suppression. LASSO regression identified VOC-producing and antagonistic microbes as predictors associated with BSR incidence, whereas correlation analysis revealed a significant negative association only for VOC-producing microbes (r=-0.60, p=0.02). Nitrogen-fixing microbes were positively associated with disease severity (r=0.63, p=0.01). Although causality was not tested, the results suggest that reduced BSR incidence was more closely associated with specific functional microbial groups, particularly VOC-producing microbes, than with overall microbial abundance or diversity, emphasizing that soil management strategies that support beneficial functional microbial groups may contribute to enhanced soil resilience.